Triglycerides as a mediator in the hyperuricemia-diabetes link: insights from a hypertensive Chinese population - Lu, Dan; Ou, Xiaowen; Wang, Tingjun; Xu, Guoyan (Frontiers in Endocrinology, 2025)
BackgroundThis study investigates whether triglycerides mediate the association between hyperuricemia and Type 2 Diabetes Mellitus (T2DM) in a hypertensive Chinese population. By comparing individuals with and without diabetes and applying generalized structural equation modeling (GSEM), we aimed to clarify the indirect effects of hyperuricemia via triglyceride pathways.MethodsA total of 274 hypertensive diabetic patients were assessed for clinical and biochemical profiles. The study included clinical categorization of DM status, demographic analysis, generalized structural equation modeling (GSEM) for mediation analysis, and regression modeling to identify diabetes risk factors.ResultsDiabetic individuals exhibited significantly higher triglyceride levels (P=0.005). Age ≥65 years was a notable demographic risk factor compared to those aged 32–49 years (OR=6.35, 95% CI: 1.26–31.97). Occasional smoking also increased DM risk (OR=3.92, 95% CI: 1.00–15.35), while alcohol consumption showed no significant association. Hyperuricemia was positively associated with elevated triglyceride levels (coefficient = 0.67, P=0.01), which, in turn, significantly increased DM risk (coefficient = 1.29, P < 0.001). Although the direct effect of hyperuricemia on DM was not statistically significant (coefficient = -0.61, P=0.10), the indirect effect mediated by triglycerides was substantial (coefficient = 0.87, P=0.04). BMI categorization significantly influenced both hyperuricemia and triglyceride levels, with the highest BMI category (≥27) exhibiting the greatest prevalence (60.26% and 38.46%, respectively). However, the direct association between BMI and DM was not statistically significant (P=0.407), suggesting the involvement of mediating factors.ConclusionTriglycerides play a key mediating role in the relationship between hyperuricemia and Type 2 DM among hypertensive patients. BMI is significantly associated with hyperuricemia and triglyceride levels, although not directly with DM. These findings emphasize the need for targeted interventions focused on lipid regulation, weight control, and lifestyle modifications to prevent diabetes progression in this high-risk population.